Challenges of Caring for an Advanced Chronic Kidney Disease Patient with Severe Thrombocytopenia. Issue 6 (January 2013) - Akimoto, Tetsu; Ito, Chiharu; Kotoda, Atsushi; Ogura, Manabu; Sugase, Taro; Sato, Ryuta; Kusano, Eiji; Nagata, Daisuke
An autogenous arteriovenous fistula has been considered to be the optimal form of vascular access for hemodialysis (HD) in the field of nephrology. Nevertheless, the decision regarding the type of access, whether it be an arteriovenous fistula, an arteriovenous graft, or a central venous catheter, must still be individualized. In the present report, we describe the case of a female patient with advanced chronic kidney disease (CKD) associated with a hemostatic disorder. Despite the exhausted peripheral vasculature, she required recurrent platelet transfusions for severe thrombocytopenia due to aplastic anemia. The goal of care for this patient was to optimize the dialysis treatment without increasing the bleeding risk. Various concerns regarding the therapeutic conundrums encountered in the case are also discussed.